Potensi Antioksidan Dari Ekstrak Etanol Kulit Buah Asam Jawa (Tamarandus Indica L.) sebagai Anti Aging Dalam Sediaan Kosmetik Gel - Lubis, Minda Sari; Yuniarti, Rafita; Rani, Zulmai; Andjelie, Tiara; Zulhij, Fizrya (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Skin aging can be caused by intrinsic factors which are aging processes that take place naturally and extrinsic factors caused by environmental influences such as sunlight, air, chemicals and the surrounding environment. Prevention of premature aging can be done by giving anti-oxidants, especially herbal skin care products and anti-oxidant cosmetic preparations. plants and spices. One plant that functions as an anti-oxidant is tamarind fruit (Tamarindus indica L.) is a plant with the family Mimosaceae. The method used in this study is a preparation made based on the standard formula of Na-CMC gel base according to Muttiin (2021), a gel standard formula based on Sodium Carboxymethyl cellulose (Na-CMC) based on % w/w. The results of research on the physical characteristics of gel preparations concluded that the gel preparation of Java Tamarind Fruit Skin Ethanol Extract (Tamarindus Indica L.) has met the physical quality standards of facial gel preparations. Gel preparation of Java Tamarind Fruit Skin Ethanol Extract (Tamarindus Indica L.) can provide anti-aging effects which can improve skin condition in the first week.